Growing energy on the farm - Hager, Claus-Peter (Technical Centre for Agricultural and Rural Cooperation, 2008)
Unwanted plant species have taken over huge areas of Namibian farmland. Rather than being a problem, the encroaching bush is now seen as a potential source of energy for a small-scale power station.